Sisal fiber-based fluorescent carbon dots, preparation method thereof and application of sisal fiber-based fluorescent carbon dots in dye adsorption

By growing fluorescent carbon dots in situ on sisal fibers, an efficient adsorption material was prepared, which solved the problem of low adsorption ability of existing modified sisal fiber composites in dye adsorption, and achieved efficient adsorption and good regeneration properties of methyl blue dyes.

CN119588311APending Publication Date: 2025-03-11SUQIAN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411692781.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing modified sisal fiber composites have the problem of low adsorption ability in dye adsorption, and the preparation of high-efficiency adsorption materials is of great significance to their practical application.

Method used

By growing fluorescent carbon dots in situ on sisal fibers, high-strength, surface-rich functional groups, and excellent pore structure sisal fiber-based fluorescent carbon dot materials (SF-N-CDs) were prepared by microwave method, and applied to the adsorption of methyl blue dye.

Benefits of technology

Excellent adsorption performance to methyl blue dye was achieved, with a maximum adsorption amount of 619.7 mg/g, which is about 3.9 times that of unprocessed sisal fibers, and good regeneration performance and selective adsorption ability were shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588311A_ABST
    Figure CN119588311A_ABST
Patent Text Reader

Abstract

The invention discloses sisal fiber-based fluorescent carbon dots and a preparation method and application thereof in dye adsorption, and the preparation method comprises the following steps: step 1, adding sisal fibers into a mixed solution composed of sodium hypochlorite, TEMPO, sodium bromide and deionized water, adjusting the pH value to 9-10, reacting at room temperature for 4 hours, then quenching the reaction with ethanol, washing the obtained mixture with tap water to neutralize, and drying to obtain sisal fiber-based fluorescent carbon dots; washing with deionized water, and drying to obtain carboxylated sisal fiber; step 2, taking the carboxylated sisal fibers as a carbon source, adding polyethyleneimine as a nitrogen source, and performing microwave treatment to obtain the sisal fiber-based fluorescent carbon dots. According to the invention, CDs are grown on SF in situ by a simple microwave method, the SF-N-CDs material with high strength, rich functional groups on the surface and high pore structure is obtained, and the adsorption capacity of the SF-N-CDs material on methyl blue dye can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon nanomaterials, and more specifically to sisal fiber-based fluorescent carbon dots, a preparation method thereof, and an application thereof in dye adsorption. Background Art

[0002] SF is an excellent natural wood cellulose fiber with high cellulose content, chemical functional groups and porous structure. It is also inexpensive, durable and easy to recycle, making it a first choice for adsorption purposes. For example, DosSantos et al. used SF to adsorb cadmium (II) and lead (II) in water, with adsorption capacities of 1.85 mg / g and 1.34 mg / g, respectively. Vargas et al. confirmed the excellent removal ability of SF for methylene blue (MB) and reactive black 5 (RB5) dyes. In addition, Teklu et al. deposited polyaniline on the surface of sisal fibers for the removal of Pb from water. 2+ ions, with a maximum adsorption capacity of 6.53 mg / g. These studies show that SF can adsorb and remove dyes or metal ions from wastewater. However, most modified SF composites still have the disadvantage of low adsorption capacity, and the preparation of SF-based composites with high adsorption efficiency is of great significance for their practical application. Summary of the invention

[0003] An object of the present invention is to solve at least the above problems and to provide at least the advantages which will be described hereinafter.

[0004] An object of the present invention is to provide a sisal fiber-based fluorescent carbon dot, a preparation method and an application in dye adsorption, which adopts a simple microwave method to in situ grow CDs on SF to prepare a sisal fiber-based carbon dot material (SF-N-CDs) with high strength, rich surface functional groups (amino, carboxyl, hydroxyl) and high porous structure, and apply it to the adsorption of methyl blue dye.

[0005] In order to achieve these purposes and other advantages of the present invention, according to one aspect of the present invention, the present invention provides a method for preparing sisal fiber-based fluorescent carbon dots, comprising:

[0006] Step 1, adding sisal fiber to a mixed solution of sodium hypochlorite, TEMPO, sodium bromide and deionized water, adjusting the pH to 9-10, reacting at room temperature for 4 hours, then quenching the reaction with ethanol, washing the resulting mixture with tap water for neutralization, then washing with deionized water, and drying to obtain carboxylated sisal fiber;

[0007] Step 2: Using carboxylated sisal fiber as a carbon source, adding polyethyleneimine as a nitrogen source, and obtaining sisal fiber-based fluorescent carbon dots by microwave treatment.

[0008] Preferably, in the step 2, carboxylated sisal fiber is used as a carbon source, polyethyleneimine is added as a nitrogen source, and the microwave treatment method includes: adding polyethyleneimine to deionized water and completely dissolving it; then adding carboxylated sisal fiber and mixing, and placing the mixture in a microwave at 80-100°C and 600W and reflux for 40-60 minutes; then washing the product with tap water to neutralize the pH value, and then washing the product with deionized water and drying it to obtain sisal fiber-based fluorescent carbon dots.

[0009] Preferably, in step 2, the weight ratio of the carboxylated sisal fiber to the polyethyleneimine is 2:0.5-1.

[0010] Preferably, in step 1, the weight ratio of the sisal fiber:TEMPO:sodium hypochlorite:sodium bromide is 8:0.01-0.03:5-7:0.1-0.3.

[0011] The present invention also provides a sisal fiber-based fluorescent carbon dot sisal fiber-based fluorescent carbon dot, which is prepared by the above-mentioned preparation method.

[0012] According to another aspect of the present invention, the present invention provides an application of sisal fiber-based fluorescent carbon dots in dye adsorption, which is used for adsorbing methyl blue dye.

[0013] Preferably, the sisal fiber-based fluorescent carbon dots can regenerate and cyclically adsorb the methyl blue dye using a 0.1 M NaOH solution as an elution reagent.

[0014] Preferably, the sisal fiber-based fluorescent carbon dots are used to separate and adsorb methyl blue dye from a mixed dye of methyl blue, rhodamine B and / or safranin T.

[0015] The present invention has at least the following beneficial effects:

[0016] The present invention uses deionized water as a dispersion medium and biomass sisal fiber (SF) as a matrix material, and adopts simple and environmentally friendly microwave synthesis to successfully prepare a sisal fiber-based fluorescent carbon dot material that emits yellow fluorescence. The introduction of fluorescent carbon dots introduces abundant polar groups such as -OH, -NH2, and -COOH on the surface of SF, greatly increasing the adsorption sites of the material. The sisal fiber-based carbon dot material has excellent adsorption performance for methyl blue dye, and the maximum adsorption amount reaches 619.7 mg / g, which is about 3.9 times the adsorption amount of unprocessed SF. In addition, the carbon dot material uses 0.1M NaOH solution as an elution reagent, exhibits good regeneration performance, is easy to elute, and after six adsorption-regeneration cycles, the removal rate remains above 70%. In addition, the carbon dot material can also separate methyl blue dye from a mixed solution of rhodamine B and safranin T dyes, and is an ideal selective adsorption material. In addition, the synthesis method of the sisal fiber-based carbon dot material is simple, does not require organic solvents, is easy to industrialize, can be recycled at least 6 times, and has a lower cost. Therefore, the practical application prospects of this adsorbent material in the field of wastewater treatment are very broad.

[0017] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 FT-IR spectra of sisal fiber (SF), carboxylated sisal fiber (SF-COOH) and sisal fiber-based fluorescent carbon dots (SF-N-CDs) in Example 1 of the present application; it can be seen from the figure that the broad characteristic band of SF at 3334cm-1 can be attributed to the -OH stretching in cellulose, hemicellulose and monosaccharides. After the introduction of the -COOH group, the infrared spectrum of SF-COOH shows a significant sharpening of the C=O characteristic peak at 1731cm-1. When SF-COOH reacts with PEI, the carboxylate C=O stretching vibration peak disappears in the infrared spectrum of SF-N-CDs, and a new absorption peak appears at 1467cm-1, indicating the characteristic C=O peak in the amide. Therefore, the data confirms the successful introduction of nitrogen-doped CDs on SF.

[0019] Figure 2 The XRD spectra of sisal fiber (SF), carboxylated sisal fiber (SF-COOH) and sisal fiber-based fluorescent carbon dots (SF-N-CDs) in Example 1 of the present application are shown in Figure 1. It can be seen from the figure that SF-COOH and SF-N-CDs show similar XRD spectra to the raw material SF, but SF-N-CDs shows the highest intensity. This intensity can be attributed to the superposition of the crystallization peak of CDs and the crystallization peak of SF.

[0020] Figure 3To test the effect of different pH values ​​on the adsorption of methyl blue by SF-N-CDs.

[0021] Figure 4 This is the effect of SF-N-CDs, SF-COOH, and SF on the adsorption of methyl blue.

[0022] Figure 5 The effect of different adsorption times on the adsorption of methyl blue by SF-N-CDs.

[0023] Figure 6 The effect of different dye concentrations on the adsorption performance of SF-N-CDs.

[0024] Figure 7 Repeated use effect of SF-N-CDs.

[0025] Figure 8 This is the effect of temperature on the adsorption of methyl blue dye by SF-N-CDs.

[0026] Fig. 9 Schematic diagram of digital photograph of the selective adsorption of SF-N-CDs.

[0027] Fig.10 This is the selective adsorption effect of SF-N-CDs. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0029] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0030] The present application provides a method for preparing sisal fiber-based fluorescent carbon dots, comprising:

[0031] Step 1: Add sisal fiber to a mixed solution of TEMPO, sodium hypochlorite, sodium bromide, and deionized water, adjust the pH to 9-10, react at room temperature for 4 hours, then terminate the reaction by quenching oxidation with ethanol, wash the resulting mixture with tap water to neutralize, then wash with deionized water, and dry to obtain carboxylated sisal fiber. The weight ratio of sisal fiber: TEMPO: sodium hypochlorite: sodium bromide is 8: 0.01-0.03: 5-7: 0.1-0.3;

[0032] Step 2: Using carboxylated sisal fiber as a carbon source, adding polyethyleneimine as a nitrogen source, and obtaining sisal fiber-based fluorescent carbon dots by microwave treatment.

[0033] In step 2, carboxylated sisal fiber is used as a carbon source, polyethyleneimine is added as a nitrogen source, and the microwave treatment method includes: adding polyethyleneimine to deionized water and completely dissolving it; then adding carboxylated sisal fiber and mixing it, placing the mixture in a microwave at 80-100°C and 600W for reflux for 40-60 minutes; then washing the product with tap water to neutralize the pH value, and then washing the product with deionized water and drying it to obtain sisal fiber-based fluorescent carbon dots. The weight ratio of carboxylated sisal fiber to polyethyleneimine is 2:0.5-1. Specific embodiment 1:

[0035] Step 1, add 8 grams of sisal fiber (SF) to a mixed solution consisting of 0.02 grams of TEMPO, 6.5 grams of sodium hypochlorite, 0.2 grams of sodium bromide, and 700 milliliters of deionized water, adjust the pH to about 10 with 2M NaOH, stir and react at room temperature for 4 hours, then quench the oxidation with 4 mL of ethanol to terminate the reaction, wash the resulting mixture with tap water to neutrality, then wash with deionized water, and dry naturally to obtain carboxylated sisal fiber (SF-COOH);

[0036] Step 2: Add 1.0 g of polyethyleneimine into 150 ml of deionized water and dissolve it completely; then add 2 g of carboxylated sisal fiber and mix, and reflux the mixture in a microwave at 100°C and 600 W for 50 minutes; then wash the product with tap water to neutralize the pH value, then wash the product with deionized water and dry it naturally to obtain sisal fiber-based fluorescent carbon dot material (SF-N-CDs).

[0037] Adsorption test 1

[0038] Prepare methyl blue dye with a concentration of 200 mg / L and a volume of 20 mL, then adjust the pH value of the dye solution with 0.1 M hydrochloric acid and 0.1 M NaOH, add 30 mg of SF-N-CDs, and shake on a shaker at 25 ° C for 12 hours. Test the effect of different pH values ​​on the adsorption of methyl blue by SF-N-CDs. The results are as follows: Figure 3 As shown in the figure, it can be seen that under neutral conditions, SF-N-CDs has the best adsorption capacity for methyl blue dye.

[0039] Adsorption test 2

[0040] The concentration of methyl blue dye was 800 mg / L, and the volume was 15 mL. Three adsorbents, SF-N-CDs, SF-COOH, and SF, were added and placed in a shaker for 200 min. The adsorption capacity was tested to investigate the effect of the adsorbent on the adsorption capacity of methyl blue. The results are as follows: Figure 4As shown, it can be seen that the adsorption amount of the raw material SF is the lowest. After the fluorescent carbon dots are introduced into SF, the adsorption amount is 619.7 mg / g, which is about 3.9 times the adsorption amount of SF. It can be seen that after the carbon dots containing a large number of polar functional groups are introduced into SF, the adsorption amount is greatly improved.

[0041] Adsorption test 3

[0042] Prepare methyl blue dye with a concentration of 50 mg / L and a volume of 50 mL. Add 30 mg of SF-N-CDs at room temperature. Stir magnetically at a speed of 150 rpm to test the effect of different adsorption times on the adsorption of methyl blue by SF-N-CDs. The results are as follows: Figure 5 As shown, it can be seen that the adsorption basically reached adsorption equilibrium after 200 minutes of adsorption. As the time continued to extend, the adsorption amount increased less. It can be seen that the adsorption rate of SF-N-CDs for methyl blue dye was faster.

[0043] Adsorption test 4

[0044] Different concentrations of methyl blue dye were prepared in a volume of 15 mL, 10 mg of SF-N-CDs was added, and the mixture was shaken in a shaker (150 r / min) at 25 °C for 300 min. The absorbance of the supernatant was measured using a UV spectrophotometer to investigate the effect of different dye concentrations on the adsorption performance. The results are as follows: Figure 6 As shown, when the initial concentration of the dye is 800 mg / L, the maximum adsorption amount of methyl blue by SF-N-CDs reaches 619.7 mg / g.

[0045] Adsorption test 5

[0046] Prepare 200mg / L of methyl blue dye, 15mL, add 20mg of SF-N-CDs, place it in a shaker at room temperature for 200min of vibration adsorption, test the absorbance of the supernatant to calculate its removal rate, and then desorb the sisal fiber adsorbed with 15mL of 0.1MnaOH solution, shake it on a shaker for 1 hour, and after the dye is desorbed, add the same concentration and volume of methyl blue dye again for adsorption. According to this method, the number of times SF-N-CDs are reused is investigated, and the results are as follows: Figure 7 As shown, the results show that the SF-N-CDs can be reused at least 6 times and can still maintain a good removal rate. Even after six consecutive adsorption regeneration cycles, the removal efficiency remains at 70.9%.

[0047] Adsorption test 6

[0048] The effect of different temperatures on the maximum adsorption capacity was investigated. 15 mL of methyl blue dye was prepared, 20 mg of SF-N-CDs was added, and the mixture was vibrated for 200 min at different temperatures. The absorbance of the supernatant was tested and the adsorption capacity was determined. The maximum adsorption capacity at three temperatures, namely 25°C, 35°C, and 45°C, was investigated. The results are as follows: Figure 8 As shown, it can be seen that the adsorption amount of methyl blue dye by SF-N-CDs increases with the increase of temperature.

[0049] Adsorption test 7

[0050] The selective adsorption performance of SF-N-CDs for dyes was studied. Rhodamine B and safranin T were selected as the mixed system. Methyl blue (MeB), rhodamine B (RhB) and safranin T (ST) were prepared with a concentration of 10 mg / L, 10 mL each. Then, methyl blue was mixed with rhodamine B and safranin T, respectively. 20 mg SF and 20 mg SF-N-CDs were added to the two mixed dyes, respectively. The mixture was placed in a shaker at room temperature for 200 min. First, visual observation showed that SF had poor selectivity and little color change, while SF-N-CDs had good selectivity. Its digital photo is shown in Figure 2. Fig. 9 As shown in Figure 2, after adsorption, the colors of ST and RhB were reduced, while SF-N-CDs were attached with blue. The good selectivity of SF-N-CDs was further verified by UV spectrophotometer, and the test results are shown in Figure 2. Fig.10 As shown, no MeB was detected in the mixed dye solution after adsorption, which indicates that SF-N-CDs have high selectivity in separating MeB from ST and RhB.

[0051] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A method for preparing sisal fiber-based fluorescent carbon dots, characterized in that: include: Step 1, adding sisal fiber to a mixed solution of sodium hypochlorite, TEMPO, sodium bromide and deionized water, adjusting the pH to 9-10, reacting at room temperature for 4 hours, then quenching the reaction with ethanol, washing the resulting mixture with tap water for neutralization, then washing with deionized water, and drying to obtain carboxylated sisal fiber; Step 2: Using carboxylated sisal fiber as a carbon source, adding polyethyleneimine as a nitrogen source, and obtaining sisal fiber-based fluorescent carbon dots by microwave treatment.

2. The method for preparing sisal fiber-based fluorescent carbon dots according to claim 1, characterized in that: In the step 2, carboxylated sisal fiber is used as a carbon source, polyethyleneimine is added as a nitrogen source, and the microwave treatment method includes: adding polyethyleneimine into deionized water and completely dissolving it; then adding carboxylated sisal fiber and mixing it, placing the mixture in a microwave at 80-100°C and 600W and refluxing for 40-60 minutes; then washing the product with tap water to neutralize the pH value, and then washing the product with deionized water and drying it to obtain sisal fiber-based fluorescent carbon dots.

3. The method for preparing sisal fiber-based fluorescent carbon dots according to claim 1, characterized in that: In the step 2, the weight ratio of the carboxylated sisal fiber to polyethyleneimine is 2:0.5-1.

4. The method for preparing sisal fiber-based fluorescent carbon dots according to claim 1, characterized in that: In the step 1, the weight ratio of the sisal fiber: TEMPO: sodium hypochlorite: sodium bromide is 8: 0.01-0.03: 5-7: 0.1-0.

3.

5. Sisal fiber-based fluorescent carbon dots, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 4.

6. Application of sisal fiber-based fluorescent carbon dots in dye adsorption, characterized in that: The sisal fiber-based fluorescent carbon dots prepared by the preparation method according to any one of claims 1 to 4 adsorb methyl blue dye.

7. The use of sisal fiber-based fluorescent carbon dots in dye adsorption as claimed in claim 6, characterized in that: The sisal fiber-based fluorescent carbon dots can regenerate and cyclically adsorb methyl blue dye by using 0.1M NaOH solution as an elution reagent.

8. The use of sisal fiber-based fluorescent carbon dots in dye adsorption as claimed in claim 6, characterized in that: The sisal fiber-based fluorescent carbon dots are used for separating and adsorbing methyl blue dye in a mixed dye of methyl blue, rhodamine B and / or safranin T.